A MODEL FOR THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN A MULTIMODAL LEARNING ENVIRONMENT: A MODEL FOR THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN A MULTIMODAL LEARNING ENVIRONMENT - Koldybaeva, Zalina (Журнал иностранных языков и лингвистики, 2025)
The formation of foreign language communicative competence plays an important role in the development of modern foreign language education. Recently, there has been an increasing focus on multimodal learning, which implies a combination of various channels of perception. Unlike traditional teaching methods, multimodal learning environments combine various elements, such as visual, auditory, kinematic, and digital elements, which makes the educational process more effective and interesting. In this environment, students improve their memorization, activate various channels of perception, and create real conditions for interaction. Thus, multimodal education has a significant impact on the development of students’ communication skills.